Environmentally friendly antibacterial acrylic emulsion and preparation method thereof

By introducing composite antibacterial agents and nanotitanium oxide into the acrylic emulsion, the problem of bacteria breeding during storage of the acrylic emulsion is solved, and excellent antibacterial and environmentally friendly properties are achieved.

CN119751744APending Publication Date: 2025-04-04ZIBO KUNHAN FINE CHEM INSTALLATION CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510022653.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing acrylic emulsions are prone to breeding bacteria during storage or use, resulting in reduced quality and lack of antibacterial properties.

Method used

The preparation method of environmentally friendly antibacterial acrylic emulsion is adopted, including the use of acrylate monomers, organic acids, composite antibacterial agents, emulsifiers, initiators and deionized water, and the composite antibacterial agents are prepared through carbonization treatment, vacuum impregnation, magnetic stirring, drying and modification treatment. Combined with the ultraviolet light absorption performance of nano-titanium oxide, an emulsion with antibacterial effect is formed.

Benefits of technology

The prepared acrylic emulsion has excellent antibacterial properties, can effectively prevent microorganisms from growing, extend storage time, maintain stable performance, and meet environmental standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751744A_ABST
    Figure CN119751744A_ABST
Patent Text Reader

Abstract

The invention discloses an environmentally friendly antibacterial acrylic emulsion and a preparation method thereof. The acrylic emulsion comprises the following components: an acrylic ester monomer, an organic acid, a composite antibacterial agent, an emulsifier, an initiator and deionized water. The acrylic emulsion prepared by the invention has excellent antibacterial performance and can effectively inhibit the growth of various microorganisms such as bacteria, fungi, molds and yeasts, thereby effectively preventing the acrylic emulsion from deteriorating and reducing its performance due to the growth of microorganisms during storage or use of the acrylic emulsion, greatly prolonging the storage time of the acrylic emulsion, and maintaining the stability of its performance during storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of acrylic emulsions, in particular to an environmentally friendly antibacterial acrylic emulsion and a preparation method thereof. Background Art

[0002] Acrylic emulsion is a milky white or nearly transparent viscous liquid. Formed by the copolymerization of pure acrylic ester monomers, it offers small particle size, versatility, and exceptional performance. Suitable for a wide range of coating formulations, it exhibits outstanding water and weather resistance, particularly in high-gloss and semi-gloss coatings. Acrylic emulsion also exhibits excellent water, alkali, and stain resistance, and exhibits excellent adhesion to a wide variety of surfaces.

[0003] The prior art application publication number is CN 107163181 A, which discloses that "the present invention discloses an acrylic emulsion and a preparation method thereof, wherein the acrylic emulsion comprises, by weight, 45-90 parts of a soft monomer, 1-40 parts of a hard monomer, 1-10 parts of a functional monomer, 0-1 part of a molecular weight regulator, 30-55 parts of a solvent, 0.1-3 parts of an initiator, 0.1-2 parts of a buffer, 0.1-1 part of a reducing agent, 0.1-1 part of an oxidizing agent, 0.1-10 parts of an anionic emulsifier, 0.1-5 parts of a nonionic emulsifier, and 0.1-5 parts of a reactive emulsifier. The acrylic emulsion of the present invention has strong adhesion to polyvinyl chloride film and can prevent degumming." However, it does not have antibacterial properties and is prone to bacterial growth during storage or subsequent use, resulting in a significant reduction in the quality of the acrylic emulsion.

[0004] Therefore, the present invention solves the corresponding problems by providing an environmentally friendly antibacterial acrylic emulsion. Summary of the Invention

[0005] The purpose of the present invention is to provide an environmentally friendly antibacterial acrylic emulsion to solve the deficiencies in the prior art.

[0006] The technical solution adopted in the present invention is as follows:

[0007] An environmentally friendly antibacterial acrylic emulsion comprises the following components in parts by weight: 60-70 parts of acrylate monomers, 13-16 parts of organic acids, 12-15 parts of composite antibacterial agents, 1-3 parts of emulsifiers, 0.22-0.25 parts of initiators, and 30-40 parts of deionized water.

[0008] As a further technical solution: the preparation method of the composite antibacterial agent comprises the following steps:

[0009] First, the polyacrylonitrile fiber is carbonized to obtain a carbonized material;

[0010] The carbonized material, nano zinc oxide and nano titanium oxide were sequentially added into deionized water, vacuum impregnated for 30 minutes, and discharged to obtain a mixed dispersion;

[0011] Sodium hydroxide solution was added to the mixed dispersion at a volume ratio of 1:1, the temperature was adjusted to 60° C., magnetic stirring was performed for 10 hours, and then the mixture was cooled to 22° C., allowed to stand for 24 hours, and then filtered to obtain a filter material;

[0012] Wherein, the mass fraction of sodium hydroxide is 10%;

[0013] The filtered material was washed with deionized water until neutral, and dried at 70° C. for 12 hours to obtain a dried material;

[0014] The obtained dried material was placed in a furnace and calcined for 2 hours to obtain a calcined material;

[0015] The calcined material is modified to obtain a composite antibacterial agent.

[0016] As a further technical solution: the carbonization treatment is:

[0017] Heat up to 450°C at a heating rate of 1°C / s and keep warm for 1 hour.

[0018] As a further technical solution: the mass ratio of the carbonized material, nano zinc oxide, nano titanium oxide and deionized water is 10-12:4-5:1-2:80-90.

[0019] As a further technical solution: the vacuum impregnation temperature is 40° C., and the vacuum degree of the vacuum impregnation is 0.1 Pa.

[0020] As a further technical solution: the calcination temperature in the horse-boiling furnace is 520°C.

[0021] As a further technical solution: the modification treatment is:

[0022] First, the calcined material was added to deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion.

[0023] The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected;

[0024] The supernatant was spray-dried to obtain.

[0025] As a further technical solution: the mixing ratio of the calcined material and deionized water is 15g:100mL;

[0026] The ultrasonic power is 2.5 kW and the frequency is 30 kHz.

[0027] As a further technical solution: the acrylic acid ester monomers are ethyl acrylate and ethyl methacrylate;

[0028] Wherein, the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1;

[0029] The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5;

[0030] The emulsifier is fatty alcohol polyoxyethylene ether;

[0031] The initiator is potassium persulfate.

[0032] A method for preparing an environmentally friendly antibacterial acrylic emulsion comprises the following steps:

[0033] S1 preparation:

[0034] Weigh the following according to parts by weight: acrylate monomer, organic acid, composite antibacterial agent, emulsifier, initiator, and deionized water;

[0035] S2 mixing emulsification:

[0036] Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, and cool to room temperature to obtain.

[0037] Beneficial effects:

[0038] The acrylic emulsion prepared by the present invention has excellent antibacterial properties and can effectively inhibit the growth of various microorganisms such as bacteria, fungi, molds, yeasts, etc., thereby effectively preventing the acrylic emulsion from deteriorating and degrading due to the growth of microorganisms during storage or use. The storage time of the acrylic emulsion can be greatly extended, and the performance stability can be maintained during storage.

[0039] The acrylic emulsion prepared by the present invention is a water-based emulsion, does not contain an organic solvent, does not release organic compounds, conforms to the current environmental protection theme, and can protect the environment and human health and safety issues.

[0040] At the same time, the acrylic emulsion prepared by the present invention can be applied to paper coating. Due to its excellent antibacterial performance, the cured coating surface can maintain high antibacterial performance for a long time, thereby preventing the growth of bacteria and algae and extending the service life.

[0041] The nano titanium dioxide component introduced into the composite antibacterial agent of the present invention can absorb ultraviolet light, reduce the aging and degradation effect of ultraviolet light on the cured acrylic emulsion product, and greatly improve the weather resistance.

[0042] The acrylic emulsion prepared by the invention has excellent film-forming property and can form a continuous, uniform and dense film. When applied to paper surface treatment, the acrylic emulsion can obtain a coating with higher adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a bar graph of the surface drying time of each test group. DETAILED DESCRIPTION

[0044] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0045] The following are specific embodiments

[0046] Example 1

[0047] A method for preparing an environmentally friendly antibacterial acrylic emulsion comprises the following steps:

[0048] S1 preparation:

[0049] Weigh the following according to their weight parts: 60 parts of acrylate monomer, 13 parts of organic acid, 12 parts of composite antibacterial agent, 1 part of emulsifier, 0.22 parts of initiator, and 30 parts of deionized water; wherein the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1; the acrylate monomer is ethyl acrylate and ethyl methacrylate;

[0050] The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5;

[0051] The emulsifier is fatty alcohol polyoxyethylene ether;

[0052] The initiator is potassium persulfate.

[0053] The preparation method of the composite antibacterial agent comprises the following steps:

[0054] First, the polyacrylonitrile fiber is carbonized to obtain a carbonized material;

[0055] The carbonized material, nano zinc oxide and nano titanium oxide were sequentially added into deionized water, vacuum impregnated for 30 minutes, and discharged to obtain a mixed dispersion;

[0056] Sodium hydroxide solution was added to the mixed dispersion at a volume ratio of 1:1, the temperature was adjusted to 60° C., magnetic stirring was performed for 10 hours, and then the mixture was cooled to 22° C., allowed to stand for 24 hours, and then filtered to obtain a filter material;

[0057] Wherein, the mass fraction of sodium hydroxide is 10%;

[0058] The filtered material was washed with deionized water until neutral, and dried at 70° C. for 12 hours to obtain a dried material;

[0059] The obtained dried material was placed in a furnace and calcined for 2 hours to obtain a calcined material;

[0060] The calcined material is modified to obtain a composite antibacterial agent; the carbonization treatment is as follows:

[0061] The temperature was raised to 450°C at a heating rate of 1°C / s and kept at that temperature for 1 hour. The mass ratio of the carbonized material, nano-zinc oxide, nano-titanium oxide and deionized water was 10:4:1:80. The vacuum impregnation temperature was 40°C and the vacuum degree was 0.1 Pa. The calcination temperature in the furnace was 520°C. The modification treatment was as follows:

[0062] First, the calcined material was added to deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion.

[0063] The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected;

[0064] The supernatant was spray-dried to obtain a mixture of calcined material and deionized water in a ratio of 15 g:100 mL;

[0065] The ultrasonic power is 2.5kW and the frequency is 30kHz;

[0066] S2 mixing emulsification:

[0067] Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, and cool to room temperature to obtain.

[0068] Example 2

[0069] A method for preparing an environmentally friendly antibacterial acrylic emulsion comprises the following steps:

[0070] S1 preparation:

[0071] Weigh the following according to their weight parts: 65 parts of acrylate monomer, 14 parts of organic acid, 13 parts of composite antibacterial agent, 2 parts of emulsifier, 0.23 parts of initiator, and 32 parts of deionized water; wherein the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1; the acrylate monomer is ethyl acrylate and ethyl methacrylate;

[0072] The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5;

[0073] The emulsifier is fatty alcohol polyoxyethylene ether;

[0074] The initiator is potassium persulfate.

[0075] The preparation method of the composite antibacterial agent comprises the following steps:

[0076] First, the polyacrylonitrile fiber is carbonized to obtain a carbonized material;

[0077] The carbonized material, nano zinc oxide and nano titanium oxide were sequentially added into deionized water, vacuum impregnated for 30 minutes, and discharged to obtain a mixed dispersion;

[0078] Sodium hydroxide solution was added to the mixed dispersion at a volume ratio of 1:1, the temperature was adjusted to 60° C., magnetic stirring was performed for 10 hours, and then the mixture was cooled to 22° C., allowed to stand for 24 hours, and then filtered to obtain a filter material;

[0079] Wherein, the mass fraction of sodium hydroxide is 10%;

[0080] The filtered material was washed with deionized water until neutral, and dried at 70° C. for 12 hours to obtain a dried material;

[0081] The obtained dried material was placed in a furnace and calcined for 2 hours to obtain a calcined material;

[0082] The calcined material is modified to obtain a composite antibacterial agent; the carbonization treatment is as follows:

[0083] The temperature was raised to 450°C at a heating rate of 1°C / s and kept at that temperature for 1 hour. The mass ratio of the carbonized material, nano-zinc oxide, nano-titanium oxide and deionized water was 11:4.5:1.5:82. The vacuum impregnation temperature was 40°C and the vacuum degree was 0.1 Pa. The calcination temperature in the furnace was 520°C. The modification treatment was as follows:

[0084] First, the calcined material was added to deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion.

[0085] The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected;

[0086] The supernatant was spray-dried to obtain a mixture of calcined material and deionized water in a ratio of 15 g:100 mL;

[0087] The ultrasonic power is 2.5kW and the frequency is 30kHz;

[0088] S2 mixing emulsification:

[0089] Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, and cool to room temperature to obtain.

[0090] Example 3

[0091] A method for preparing an environmentally friendly antibacterial acrylic emulsion comprises the following steps:

[0092] S1 preparation:

[0093] Weigh the following according to their weight parts: 68 parts of acrylate monomer, 15 parts of organic acid, 13 parts of composite antibacterial agent, 2 parts of emulsifier, 0.24 parts of initiator, and 38 parts of deionized water; wherein the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1; the acrylate monomer is ethyl acrylate and ethyl methacrylate;

[0094] The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5;

[0095] The emulsifier is fatty alcohol polyoxyethylene ether;

[0096] The initiator is potassium persulfate.

[0097] The preparation method of the composite antibacterial agent comprises the following steps:

[0098] First, the polyacrylonitrile fiber is carbonized to obtain a carbonized material;

[0099] The carbonized material, nano zinc oxide and nano titanium oxide were sequentially added into deionized water, vacuum impregnated for 30 minutes, and discharged to obtain a mixed dispersion;

[0100] Sodium hydroxide solution was added to the mixed dispersion at a volume ratio of 1:1, the temperature was adjusted to 60° C., magnetic stirring was performed for 10 hours, and then the mixture was cooled to 22° C., allowed to stand for 24 hours, and then filtered to obtain a filter material;

[0101] Wherein, the mass fraction of sodium hydroxide is 10%;

[0102] The filtered material was washed with deionized water until neutral, and dried at 70° C. for 12 hours to obtain a dried material;

[0103] The obtained dried material was placed in a furnace and calcined for 2 hours to obtain a calcined material;

[0104] The calcined material is modified to obtain a composite antibacterial agent; the carbonization treatment is as follows:

[0105] The temperature was raised to 450°C at a heating rate of 1°C / s and kept at this temperature for 1 hour. The mass ratio of the carbonized material, nano-zinc oxide, nano-titanium oxide and deionized water was 11:4:1:85. The vacuum impregnation temperature was 40°C and the vacuum degree was 0.1 Pa. The calcination temperature in the furnace was 520°C. The modification treatment was as follows:

[0106] First, the calcined material was added to deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion.

[0107] The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected;

[0108] The supernatant was spray-dried to obtain a mixture of calcined material and deionized water in a ratio of 15 g:100 mL;

[0109] The ultrasonic power is 2.5kW and the frequency is 30kHz;

[0110] S2 mixing emulsification:

[0111] Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, and cool to room temperature to obtain.

[0112] Example 4

[0113] A method for preparing an environmentally friendly antibacterial acrylic emulsion comprises the following steps:

[0114] S1 preparation:

[0115] Weigh the following according to their weight parts: 70 parts of acrylate monomer, 16 parts of organic acid, 15 parts of composite antibacterial agent, 3 parts of emulsifier, 0.25 parts of initiator, and 40 parts of deionized water; wherein the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1; the acrylate monomer is ethyl acrylate and ethyl methacrylate;

[0116] The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5;

[0117] The emulsifier is fatty alcohol polyoxyethylene ether;

[0118] The initiator is potassium persulfate.

[0119] The preparation method of the composite antibacterial agent comprises the following steps:

[0120] First, the polyacrylonitrile fiber is carbonized to obtain a carbonized material;

[0121] The carbonized material, nano zinc oxide and nano titanium oxide were sequentially added into deionized water, vacuum impregnated for 30 minutes, and discharged to obtain a mixed dispersion;

[0122] Sodium hydroxide solution was added to the mixed dispersion at a volume ratio of 1:1, the temperature was adjusted to 60° C., magnetic stirring was performed for 10 hours, and then the mixture was cooled to 22° C., allowed to stand for 24 hours, and then filtered to obtain a filter material;

[0123] Wherein, the mass fraction of sodium hydroxide is 10%;

[0124] The filtered material was washed with deionized water until neutral, and dried at 70° C. for 12 hours to obtain a dried material;

[0125] The obtained dried material was placed in a furnace and calcined for 2 hours to obtain a calcined material;

[0126] The calcined material is modified to obtain a composite antibacterial agent; the carbonization treatment is as follows:

[0127] The temperature was raised to 450°C at a heating rate of 1°C / s and kept at that temperature for 1 hour. The mass ratio of the carbonized material, nano-zinc oxide, nano-titanium oxide and deionized water was 12:5:2:90. The vacuum impregnation temperature was 40°C and the vacuum degree was 0.1 Pa. The calcination temperature in the furnace was 520°C. The modification treatment was as follows:

[0128] First, the calcined material was added to deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion.

[0129] The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected;

[0130] The supernatant was spray-dried to obtain a mixture of calcined material and deionized water in a ratio of 15 g:100 mL;

[0131] The ultrasonic power is 2.5kW and the frequency is 30kHz;

[0132] S2 mixing emulsification:

[0133] Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, and cool to room temperature to obtain.

[0134] Comparative Example 1:

[0135] Based on the technical solution of Example 1, the difference from the technical solution of Example 1 is that no composite antibacterial agent is added.

[0136] Comparative Example 2:

[0137] Based on the technical solution of Example 1, the difference from the technical solution of Example 1 is that the composite antibacterial agent is replaced by an equal amount of zinc oxide.

[0138] test:

[0139] The particle size of the sample emulsion was tested.

[0140] Table 1

[0141] Emulsion particle size nm Example 1 121 Example 2 128 Example 3 130 Example 4 126

[0142] As can be seen from Table 1, the acrylic emulsion prepared in the present invention has a relatively low emulsion particle size and good dispersibility.

[0143] Equal amounts of the Example and Comparative Example emulsions were applied to glass plates, and the surface drying time was compared. The surface drying time was tested in accordance with GB / T1728.

[0144] Table 2

[0145] Surface drying time min Example 1 30.2 Example 2 30.8 Example 3 29.7 Example 4 30.3 Comparative Example 1 33.5 Comparative Example 2 34.6

[0146] It can be seen from Table 2 that the acrylic emulsion prepared in the present invention has a shorter surface dry time and a faster drying speed.

[0147] Antibacterial testing:

[0148] The antibacterial properties of the acrylic emulsions of the examples and comparative examples were tested using GB / T21866-2008.

[0149] Table 3

[0150]

[0151] It can be seen from Table 3 that the acrylic emulsion prepared by the present invention has a high antibacterial effect.

[0152] The above description is only a preferred embodiment of the present invention, but the scope of implementation of the present invention is not limited to the embodiment shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the spirit covered by the description, should be within the scope of protection of the present invention.

Claims

1. An environmentally friendly antibacterial acrylic emulsion, characterized in that: The invention comprises the following ingredients by weight: 60-70 parts of acrylate monomers, 13-16 parts of organic acids, 12-15 parts of composite antibacterial agents, 1-3 parts of emulsifiers, 0.22-0.25 parts of initiators and 30-40 parts of deionized water.

2. The environmentally friendly antibacterial acrylic emulsion according to claim 1, characterized in that: The preparation method of the composite antibacterial agent comprises the following steps: Firstly, the polyacrylonitrile fiber is carbonized to obtain a carbonized material; The carbonized material, nano zinc oxide and nano titanium oxide are sequentially added into deionized water, vacuum impregnated for 30 minutes, and then discharged to obtain a mixed dispersion; Adding sodium hydroxide solution to the mixed dispersion at a volume ratio of 1:1, adjusting the temperature to 60°C, stirring with magnetic force for 10 hours, cooling to 22°C, standing for 24 hours, and filtering to obtain a filter material; Wherein, the mass fraction of sodium hydroxide is 10%; The filtered material was washed with deionized water until it was neutral, and dried at 70° C. for 12 hours to obtain a dried material; The obtained dried material is placed in a furnace and calcined for 2 hours to obtain a calcined material; The calcined material is modified to obtain a composite antibacterial agent.

3. An environmentally friendly antibacterial acrylic emulsion as claimed in claim 2, characterized in that: The carbonization treatment is: Raise the temperature to 450°C at a heating rate of 1°C / s and keep warm for 1 hour.

4. An environmentally friendly antibacterial acrylic emulsion as claimed in claim 3, characterized in that: The mass ratio of the carbonized material, nano zinc oxide, nano titanium oxide and deionized water is 10-12:4-5:1-2:80-90.

5. The environmentally friendly antibacterial acrylic emulsion according to claim 4, characterized in that: The vacuum impregnation temperature is 40° C., and the vacuum degree of the vacuum impregnation is 0.1 Pa.

6. The environmentally friendly antibacterial acrylic emulsion according to claim 2, characterized in that: The calcination temperature in the horse-boiling furnace is 520°C.

7. The environmentally friendly antibacterial acrylic emulsion according to claim 2, characterized in that: The modification treatment is: First, the calcined material was added into deionized water and stirred and dispersed for 20 minutes to obtain a preliminary dispersion. The preliminary dispersion obtained above was pulverized by ultrasonic treatment for 1 hour, allowed to stand for 20 minutes, filtered, and the supernatant was collected; The supernatant was spray dried to obtain.

8. An environmentally friendly antibacterial acrylic emulsion as claimed in claim 7, characterized in that: The mixing ratio of the calcined material and deionized water is 15g:100mL; The ultrasonic power was 2.5 kW and the frequency was 30 kHz.

9. The environmentally friendly antibacterial acrylic emulsion according to claim 1, characterized in that: The acrylic acid ester monomers are ethyl acrylate and ethyl methacrylate; Wherein, the mixing mass ratio of ethyl acrylate and ethyl methacrylate is 3:1; The organic acid is a mixture of maleic acid and acrylic acid in a mass ratio of 1:5; The emulsifier is fatty alcohol polyoxyethylene ether; The initiator is potassium persulfate.

10. The method for preparing an environmentally friendly antibacterial acrylic emulsion according to claim 1, characterized in that: The following steps are involved: S1 Preparation: Weigh the following according to weight: acrylate monomer, organic acid, composite antibacterial agent, emulsifier, initiator, and deionized water; S2 mixing emulsification: Add acrylate monomer to deionized water, adjust the temperature to 80°C, keep warm and stir for 30 minutes, then add emulsifier and organic acid in sequence, continue stirring for 40 minutes, then add composite antibacterial agent and initiator, keep warm and stir for 2 hours, cool to room temperature to obtain.

Citation Information

Patent Citations

  • Acrylic emulsion and preparation method therefor

    CN107163181A